(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
The article considers an algorithm for selecting a statistical criterion for testing statistical hypotheses depending on the type of available data and their distribution. The presented material provides general recommendations on choosing the most appropriate method of data analysis for the most common situations.